Poverty and nutrition policy analysis: Using SPSS for survey data analysis - Salau, Sheu (International Food Policy Research Institute, 2008)
Poverty and malnutrition in Nigeria are widespread and severe, and therefore continue to be at the center stage of the development discourse. Sixty-four percent of all rural Nigerians have a consumption level below the basic-needs poverty line, while 43 percent of rural children under five years of age are stunted in their growth. Thus, many rural Nigerians live under conditions of extreme vulnerability, both economically and physically, with quite limited abilities to cope with shocks and safeguard their current level of well-being. Government efforts at reducing poverty and malnutrition have culminated into numerous programs. Prominent among them are: National Poverty Eradication Programme (NAPEP), National Economic Empowerment and Development Strategy (NEEDS), and Millennium Development Goals (MDG). While these programs are desirable, their outcomes have been mixed. If Nigeria is to achieve the first MDG of reductions in poverty, hunger, and malnutrition, and the fourth MDG of reducing child mortality, a clear understanding of the defining characteristics of the poor and malnourished, the dimensions of poverty and malnutrition, and the determinants of such poverty and malnutrition are required for more sustainable policy actions. More so, programs that aim to reduce poverty and malnutrition can only be more effective if quantitative and qualitative poverty and nutrition analysis and statistics are the basis of their design. During the planning of the Agricultural Policy Support Facility (APSF) program in Nigeria, consultations with the Federal Ministry of Agriculture and Water Resources (FMAWR) and other stakeholders identified the need to build and strengthen capacities of ministries, departments and agencies (MDAS) in poverty and nutrition policy research and analysis. This need is premised on the fact that competent planners and policy analysis experts are essential for sound and effective policy analysis and planning. To assist in ensuring that the poverty and nutrition policies and programs are supported by appropriate analysis, APSF, in collaboration with the National Bureau of Statistics, organized a 4-day training course on Poverty and Nutrition Policy Analysis, from October 6-9, 2008 at the National Bureau of Statistics’ training room. The content of the course was based on a needs assessment survey carried out earlier among the potential participants. The training hosted 24 participants from the Federal Ministry of Agriculture and Water Resources, the Federal Ministry of Health, the National Planning Commission, the National Bureau of Statistics, and research institutes and universities (see Appendix A for the list of participants). The objective of the training course was to: strengthen existing capacity across sectoral ministries and agencies in data analysis, specifically poverty and nutrition policy analysis; expand the knowledge base for developing agricultural, rural development, poverty, and nutrition related policies and programs; enable the development of advanced computing skills; and reinforce international best practices in poverty and nutrition analysis.